Stochastic Ideas Fundamental in the Colombian Curriculum - Castro Carvajal, Dicleny (Universidad Nacional del Litoral, 2021)
The curricular guidelines and basic standards of mathematics in Colombia, through the Ministry of Education, consider the teaching of statistics and probability from primary basic education, evolving conceptually through secondary and middle school. The presence of the stochastic ideas highlighted by Shaughnessy (2019) is analyzed in this study: distributions, centralization, variability and inference, as the four fundamental stochastic ideas, throughout all compulsory education. Using the content analysis methodology, it is possible to identify the stochastic ideas present in the curricular guidelines of each level of basic and secondary education. An emphasis was found on concepts associated with big ideas about statistical distributions and informal inference. However, when appearing as concepts, no relationships are established between these and the activities, processes and contexts that stimulate the development of stochastic reasoning from primary basic education.